An unexpected result of playing football: Anal laceration - Ekmekyapar, Muhammed; Gokhan Turtay, Muhammet; Oguzturk, Hakan; Gurbuz, Sukru; Ediz Sarihan, Mehmet; Yigit, Eren; Faruk Solgun, Omer (Annals of Medical Research, 2021)
None
Keywords: Anal laceration; injury; football